Motivation of agricultural workers: mechanism, features and directions of development - E. A. Pogrebtsova; V. V. Leushkina; O. V. Kondratieva (Омский научный вестник: Серия "Общество. История. Современность")
The effective activity of the enterprise is determined not only by advanced technologies, but also by the desire of employees to achieve high results. The formed mechanism of motivation of agricultural workers should contribute to increasing the productivity of workers. However, as practice shows, it does not give the proper result. The mechanism of motivation of workers engaged in agriculture has not been worked out in the specialized literature. The article presents an interpretation of the concept of «motivation» taking into account the peculiarities of agriculture. The causal relationship between motivation and motivational development of personnel is considered. The mechanism of motivation of agricultural workers has been developed on the example of an operating enterprise.